PENGARUH EARNING PER SHARE DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2014 - 2023 - Ferdyan Dwy Mustofa; Andriyani Hapsari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of Earning per Share (EPS) and Dividend Policy on the stock price of PT Hanjaya Mandala Sampoerna Tbk for the 2014–2023 period. This research employs a quantitative approach using secondary data obtained from the company’s financial statements over a ten-year period of observation. The population in this study consists of all company financial reports, while the sample was selected using a purposive sampling technique. Data analysis was carried out using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing (t-test and F-test) with the assistance of SPSS version 25 software. The results show that partially, EPS has no significant effect on stock price, as indicated by a significance value of 0.387 > 0.05 and a t-value of 0.922 < t-table value of 2.36462. Dividend Policy also has no significant effect on stock price with a significance value of 0.353 > 0.05 and a t-value of -0.994 < t-table value of 2.36462. Simultaneously, EPS and Dividend Policy do not have a significant effect on stock price, as shown by an F-value of 0.848 < F-table value of 4.74 and a significance value of 0.468 > 0.05. Therefore, it can be concluded that both partially and simultaneously, EPS and Dividend Policy do not have a significant effect on the stock price of PT Hanjaya Mandala Sampoerna Tbk during the research period.